Strategi Peningkatan Hasil Belajar PAI Materi Ayo Kita Shalat melalui Metode Pembiasaan pada Siswa di SDIT Al Islamiyah: learning outcomes - Putra Ulinuha (Inovbook, 2021)
This study aims to get an overview of the implementation of the habituation method as an effort made by PAI teachers in the material for Let's Pray class 2 semester 2 at SDIT Al Islamiyah which was carried out during the covid 19 period using the Zoom application and offline teachers. This study uses a descriptive qualitative approach. The subjects in the study were school principals, PAI teachers, students and guardians of SDIT Al Islamiyah. The techniques used were observation, participatory interviews, and documentation. The results showed that, firstly, the implementation of reading class 2 lessons through the Zoom application and offline PAI teachers the habituation method went well using the Zoom application with a duration of about 20 minutes of habituation every day and every week PAI teachers went to the homes of SDIT Al Islamiyah students. second, the supporting factor plays a very important role in the realization of the habituation method even though using the Zoom application remotely. The inhibiting factors are in various directions, both from lazy students, differences in intelligence and incomplete infrastructure in the homes of each student. Keywords: Learning Outcomes, PAI, Prayer